PENGEMBANGAN FILTER AKTIFSHUNT MENGGUNAKAN ADAPTIVE NEURO FUZZY INFERENCE SYSTEM SEBAGAI REDUKSI HARMONISA MOTOR INDUKSI 3 FASA - Ikrom, Muhammad Alfianul; Iradiratu, DPK (Universitas Pendidikan Nasional, 2018)
Non-linear loads installed in the power system will cause harmonic distortion. Harmonicdistortion in voltage and current waveforms can result in abnormal conditions in the electrical system, avariety of electrical equipment used one of them is an electric motor type motor induction. Inductionmotor is chosen because it has several advantages such as this motor is simple, cheap and easymaintenance. On the other hand induction motor 3 phase also generate harmonics. One way to solve thisharmonic problem is to use a shunt active filter. In this research will use active shunt filter which iscontrolled using Adaptive Neural Fuzzy Inference System so it is expected to have harmonic value orTotal Harmonic Distortion (THD) in accordance with international standard ie IEEE 519-1992.